RETRACTED: Moderating role of compassion in the link between fear of Coronavirus disease and mental health among undergraduate students - Zhang, Huichun; Jasim, Saade Abdalkareem; Suksatan, Wanich; Hashim Alghazali, Tawfeeq Abdulameer; Doewes, Rumi Iqbal; Jalil, Abduladheem Turki; Patra, Indrajit; Singer, Nermeen; Failoc-Rojas, Virgilio E.; Marhoon, Haydar Abdulameer; Mustafa, Yasser Fakri; Ramírez-Coronel, Andrés Alexis; et al. (Frontiers in Psychiatry, 2022)
Background: The societal challenges presented by fear related to the COVID-19 pandemic may present unique challenges for an individual’s mental health. However, the moderating role of compassion in the relationship between fear of COVID-19 and mental health has not been well studied. The present study aimed to explore the association between fear of COVID-19 and mental health, as well as test the buffering role of compassion in this relationship. Methods: The participants in this study were 325 Iranian undergraduate students (228 females), aged 18 to 25 years, who completed questionnaires posted on social networks via a web-based platform. Results: The results showed that fear of COVID-19 was positively related with physical symptoms, social function, depressive symptoms and anxiety symptoms. The results also showed that compassion was negatively associated with physical symptoms, social function, depressive symptoms and anxiety symptoms. The interaction-moderation analysis revealed that compassion moderated the relationship between fear of COVID-19 and subscale of mental health. Conclusions: Results highlight the important role of compassion in diminishing the effect of fear of COVID-19 on the mental health (physical symptoms, social function, depressive symptoms and anxiety symptoms) of undergraduate students